A critical analysis of Prophetic narrations mentioned in KAFA JAKIMs Aqidah textbooks - Muhamad Rozaimi bin Ramle (Tanjong Malim, 2019)
A critical analysis of Prophetic narrations mentioned in KAFA JAKIMs Aqidah textbooks by Muhamad Rozaimi bin Ramle